2001
DOI: 10.1210/jc.86.12.5992
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Enhances Appetite and Increases Food Intake in Humans

Abstract: Ghrelin is a recently identified endogenous ligand for the growth hormone secretagogue receptor. It is synthesized predominantly in the stomach and found in the circulation of healthy humans. Ghrelin has been shown to promote increased food intake, weight gain and adiposity in rodents. The effect of ghrelin on appetite and food intake in man has not been determined. We investigated the effects of intravenous ghrelin (5.0 pmol/kg/min) or saline infusion on appetite and food intake in a randomised double-blind c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
739
1
25

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,020 publications
(788 citation statements)
references
References 14 publications
23
739
1
25
Order By: Relevance
“…Wren et al 7 reported a 28% increase in food intake following a total intravenous dose of 1.4 nmol/kg. In our present study, we administered 3.6 nmol/kg subcutaneous ghrelin and observed a comparable 27% increase in food intake.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wren et al 7 reported a 28% increase in food intake following a total intravenous dose of 1.4 nmol/kg. In our present study, we administered 3.6 nmol/kg subcutaneous ghrelin and observed a comparable 27% increase in food intake.…”
Section: Discussionmentioning
confidence: 98%
“…4 In addition to stimulating growth hormone (GH) release, ghrelin increases food intake when administered peripherally in rodents and man. [5][6][7] Ghrelin has thus been postulated to act as a meal initiator. 4 Chronic ghrelin administration promotes adiposity and weight gain in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is secreted into the bloodstream by the stomach and intestines. Exogenous ghrelin rapidly increases food intake in rats (Wren et al, 2001a) and humans (Wren et al, 2001b). Indeed, ghrelin is as potent at stimulating feeding as neuropeptide Y. Starvation increases ghrelin plasma concentration and refeeding rapidly decreases circulating ghrelin (Ariyasu et al, 2001).…”
Section: A Role For Cephalic Phase Responses In Appetite and Satiety?mentioning
confidence: 99%
“…[4][5][6] Reduced levels have been reported in obese subjects, 7,8 whereas increased concentrations have been found in patients with anorexia nervosa. 8,9 A preprandial rise 10 and a postprandial fall 11 in ghrelin levels indicate a physiological role of food on ghrelin secretion in humans.…”
Section: Introductionmentioning
confidence: 99%